Checklist of scythridid moths (Lepidoptera, Scythrididae) of Ukraine with description of two new species - Bidzilya, Oleksiy V.; Budashkin, Yury I.; Zhakov, Aleksandr V. (Zootaxa, 2017)
An annotated list of 46 species of Scythrididae from Ukraine is given. Two species are described as new: Scythris zhakovi Bidzilya & Budashkin, sp. n. (Crimea, Kherson Region) and Scythris psammitis Bidzilya & Budashkin sp. n. (Kherson Region). 13 species are recorded from Ukraine for the first time: Scythris bifissella (Hofmann, 1889); Scythris perlucidella Nupponen & Nupponen, 2000; Scythris subaerariella (Stainton, 1867), Scythris aegrella K. Nupponen & Junnilainen, 2000, Scythris sinensis (Felder & Rogenhofer, 1875); Scythris anomaloptera (Staudinger, 1880); Scythris flaviventrella (Herrich-Schäffer, 1855); Scythris acipenserella Nupponen & Nupponen, 2000; Scythris nigridorsella K. Nupponen, 2007; Scythris mikkolai Sinev, 1993; Scythris sublaminella Nupponen & Nupponen, 2000; Scythris kasyi Hannemann, 1962; and Episcythris triangulella (Ragonot, 1874). One species remains undetermined due to lack of male. The biology of S. zhakovi sp. n., S. aegrella, S. acipenserella and S. inertella is described based on observation by the second author in Crimea. The adults and the genitalia of one or both sexes of S. anomaloptera, S. flaviventrella, S. pudorinella (Möschler, 1866), S. kasyi and S. aegrella are illustrated.